A Critical Assessment of the Sustainability of South Africa's Fiscal Policy and Related Institutional Frameworks - Ngewana, Azande (School of Economics, 2020)
Historically, there are many examples of countries that have had to deal with the unpleasant consequences of economic mismanagement. A recent example is Venezuela, which has imploded into hyperinflation. It is therefore important to consider the question of fiscal sustainability in the South African context. This study ultimately aimed to test the sustainability of South Africa’s fiscal policy and public debt, with fiscal policy defined as the satisfaction of the intertemporal budget constraint. The Augmented Dickey–Fuller test was used to assess the stationarity of national government revenue and national government expenditure – both expressed as percentages of GDP – while the Engle–Granger test was used to test the residuals of the regression between national government revenue and national government expenditure for a long-run relationship. A long-run relationship was found between these two variables, suggesting that fiscal policy and South Africa’s public debt are sustainable. However, due to weakened institutions, the South African government should remain aware that the country’s fiscal policy could easily move into unsustainable territory.